2007
DOI: 10.1002/j.2161-1874.2007.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Sobriety From the Employment Status of Dually Diagnosed Clients Who Are Opiate Dependent

Abstract: The purpose of this study was to determine the relationship between Minnesota Multiphasic Personality Inventory‐2 (E. S. Neukrug & R. C. Fawcett, 2006) profiles and employment status for clients who are opiate dependent. A discriminant function analysis indicated that employment was a predictor in maintaining sobriety after 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Census Bureau (2000). Employment for drug misusers has been associated with improved retention in treatment (Platt, 1995), increased abstinence (Ginexi, Foss, & Scott, 2003; Scorzelli, 2007; Sterling et al, 2001), and improved social functioning (Sterling et al, 2001). At the same time, drug misusers in treatment or exiting treatment face many barriers (Magura, 2003; Meara, 2006) when entering the job market.…”
Section: Introductionmentioning
confidence: 99%
“…Census Bureau (2000). Employment for drug misusers has been associated with improved retention in treatment (Platt, 1995), increased abstinence (Ginexi, Foss, & Scott, 2003; Scorzelli, 2007; Sterling et al, 2001), and improved social functioning (Sterling et al, 2001). At the same time, drug misusers in treatment or exiting treatment face many barriers (Magura, 2003; Meara, 2006) when entering the job market.…”
Section: Introductionmentioning
confidence: 99%
“…While some have found that work participation and substance use are semiautonomous from one another (Bell et al, 2002), a large amount of research finds that there is a reciprocal interaction between employment and substance use such that employment improves substance use outcomes (Alverson et al, 2000; Platt, 1995; Scorzelli, 2007; Sterling et al, 2001; Strickler et al, 2009; The TOPPS-II Interstate Cooperative Study Group, 2003; Xie et al, 2010). These findings converge with the voices of veterans who’ve described employment as a critical component of recovery from substance use (Drebing et al, 2004).…”
mentioning
confidence: 99%